PENGARUH RASIO LIKUIDITAS, SOLVABILITAS, AKTIVITAS, DAN PROFITABILITAS TERHADAP INVESTMENT OPPORTUNITY SET (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode 2014-2018) - Patabang, Angeliano Patrio; Safkaur, Otniel; Andriati, Hastutie Noor (Jurnal Akuntansi, Audit, dan Aset, 2020)
he growth of the company is an expectation desired by all parties, either by internal parties (boardof commissioners, board of directors, staff, etc.) or external parties (investors or creditors). One ofthe parameters used to determine future investments in the Investment Opportunity Set. InvestmentOpportunity Set describes the breadth of investment opportunities for a company but is highlydependent on the company's future spending options. This study was conducted to provide empiricalevidence whether the financial ratio of liquidity, solvency, activity, and profitability affectsthe Investment Opportunity Set.The population of this study is a manufacturing company listed on the Indonesia Stock Exchangewith observations from 2014 to 2018. Determination of samples using purposive samplingmethod, which is a sampling technique with certain considerations that are considered to providebetter data. The data used is sourced from the company's financial statements which can beaccessed through www.IDX.co.id and www.idnfinancials.com. The number of samples used in thisstudy was as many as 120 samples. The analysis technique used is multiple regression to obtain acomplete picture of the relationship between variables. This study used an Î± value of 5%. Based onthe results, the ratio of liquidity, solvency, and activity have influenced the InvestmentOpportunity Set with significance values of 0.009, 0.018, and 0.002, respectively. While theprofitability ratio does not affect the Investment Opportunity Set due to the value of significanceowned by 0.198.